COMPARATIVE ANALYSIS OF THE EXOSOMAL CARGO OF THE ESTROGEN-RESISTANT BREAST CANCER CELLS - S. E. Semina; N. A. Barlev; A. G. Mittenberg; M. A. Krasilnikov (Сибирский онкологический журнал)
The exosomes involvement in the pathogenesis of tumors is based on their property to incorporate into the recipient cells resulting in the both genomic and epigenomic changes.  Earlier we have shown that exosomes from different types of estrogen-independent breast  cancer cells (MCF-7/T developed by long-term tamoxifen treatment, and MCF-7/M)  developed by metformin treatment were able to transfer resistance to the parent MCF-7  cells. To elucidate the common features of the both types of resistant exosomes, the  proteome and microRNA cargo of the control and both types of the resistant exosomes were  analyzed. Totally, more than 400 proteins were identified in the exosome samples. Of these  proteins, only two proteins, DMBT1 (Deleted in Malignant Brain Tumors 1) and THBS1  (Thrombospondin-1), were commonly expressed in the both resistant exosomes (less than  5% from total DEPs) demonstrating the unique protein composition of each type of the resistant exosomes. The comparative analysis of the miRNA differentially expressed in  the both MCF-7/T and MCF-7/M resistant exosomes revealed 180 up-regulated and 202  down-regulated miRNAs. Among them, 4 up-regulated and 8 down-regulated miRNAs were  associated with progression of hormonal resistance of breast tumors. The bioinformatical  analysis of 4 up-regulated exosomal miRNAs revealed 2 miRNAs, mir- 101and mir-181b, which up-regulated PI3K signaling  supporting the key role of PI3K/Akt in the development of the resistant phenotype of breast cancer cells.